7-Oxy-3-(3,4,5-trimethoxyphenyl)coumarin substituted phthalonitrile derivatives as fluorescent sensors for detection of Fe3+ ions: Experimental and theoretical study - (:unkn) unknown (ELSEVIER SCIENCE SA, 2014)
The novel 7-hydroxy-3-(3,4,5-trimethoxyphenyl) coumarin (1) has been synthesized via Perkin reaction and its phthalonitrile derivatives (2, 3, 4 and 5) have also been prepared from the reaction of this coumarin (1) with 3-nitrophthalonitrile, 4-nitrophthalonitrile or 4,5-dichlorophthalonitrile compounds for the first time in this study. The newly synthesized compounds have been fully characterized by H-1 NMR, MALDI-TOF, FT-IR, UV-vis and fluorescence spectral data as well as elemental analysis. The exact structure of the coumarin substituted phthalonitrile derivatives (2, 3 and 5) have also been determined using X-ray diffraction. The electronic absorption and fluorescence properties of these new compounds have been studied in different solvents. The chemosensor behaviors of these compounds to metal ions have also been examined by fluorescence spectroscopy and these compounds exhibited as fluorescence chemosensor for the determination of Fe3+ ions in solution. Fe3+ complex structures of mono-coumarin ring substituted derivatives (1-4) have been investigated by using density functional theory computations. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Coumarin (2H-chromen-2-one); Phthalonitrile, Fluorescence; Chemosensor; Fe3+ ions; TURN-ON; CHEMOSENSOR